Perfusion computed tomography of intracranial meningiomas: In vivo correlation of cerebral blood volume and vascular permeability. Issue 3 (June 2015) - Granata, Francesca; Morabito, Rosa; Alafaci, Concetta; Barresi, Valeria; Tomasello, Francesco; Vinci, Sergio; Mormina, Enricomaria; Calamuneri, Alessandro; Grasso, Giovanni; Salpietro, Francesco Maria; Longo, Marcello
Background: A noninvasive method to predict the grade of a meningioma would be desirable since it would anticipate information about tumour nature, recurrence and improve tumour management and outcomes. The aim of the present study was to assess the ability of perfusion computed tomography (PCT) technique in predicting the meningioma grade before surgery. Data from PCT, such as cerebral blood volume (CBV) and permeability surface (PS), were correlated with immunohistolopathological information. Methods: Twenty-three patients with a diagnosis of intracranial meningioma underwent PCT for pre-surgical evaluation of CBV and PS. During surgery, samples from the centre and periphery of the tumour were obtained. Two correspondent regions of interest (ROIs) were drawn on CBV and PS maps. Central and peripheral CBV and PS mean values were calculated. PCT parameters were correlated to CD-34 and endoglin. Results: There was a positive correlation between PS and CD-34. No correlation was found between PS values and endoglin, CBV values and CD-34 and endoglin values. Conclusion: Our findings suggest that PCT may support conventional morphological imaging in predicting meningioma grading before surgery.